Criminal Accountability of Love Scamming Perpetrators in Fictitious Investment Schemes Through Online Dating Applications - Zahra Ersyah Novita; Yuliana Yuli Wahyuningsih (Jurnal Daulat Hukum, 2026)
Information technology has made social activities easier, such as finding a partner through online dating apps. However, this convenience has also allowed new types of crimes to emerge, one of which is fraud using fake investments. The purpose of this study is to examine various forms of criminal liability for love scam perpetrators and the legal protections provided to victims in Indonesia. Normative legal research using regulatory methodology and case studies of relevant court decisions was used. The results indicate that individuals who commit love scams can be held criminally liable because their actions are characterized by fraud and electronic transmission. Furthermore, law enforcement for this crime faces challenges, particularly in terms of providing evidence and identifying perpetrators. To raise public awareness of similar crimes in the future, this study finds that law enforcement must be more effective by improving regulations and digital literacy.